The mediating effect of somatic symptom disorder between psychological factors and quality of life among Chinese breast cancer patients - Li, Zimeng; Zhang, Yening; Pang, Ying; He, Yi; Song, Lili; Wang, Yan; He, Shuangzhi; Tang, Lili (Frontiers in Psychiatry, 2023)
Objective We conducted this cross-sectional study to explore the mediating and predicting role of somatic symptom disorder (SSD) between psychological measures and quality of life (QOL) among Chinese breast cancer patients. Methods Breast cancer patients were recruited from three clinics in Beijing. Screening tools included the Patient Health Questionnaire-15 (PHQ-15), the Patient Health Questionnaire-9 (PHQ-9), the General Anxiety Disorder-7 scale (GAD-7), the Health Anxiety Scale (Whiteley Index-8, WI-8), the Somatic Symptom Disorder B-Criteria Scale (SSD-12), the Fear of Cancer Recurrence scale (FCR-4), the Brief Illness Perception Questionnaire (BIPQ-8), and the Functional Assessment of Cancer Therapy-Breast (FACT-B). Chi-square tests, nonparametric tests, mediating effect analysis, and linear regression analysis were used for the data analysis. Results Among the 264 participants, 25.0% were screened positive for SSD. The patients with screened positive SSD had a lower performance status, and a greater number of patients with screened positive SSD received traditional Chinese medicine (TCM) (p < 0.05). Strong mediating effects of SSD were found between psychological measures and QOL among patients with breast cancer after adjusting for sociodemographic variables as covariates (p < 0.001). The range of the percentage mediating effects was 25.67% (independent variable = PHQ-9) to 34.68% (independent variable = WI-8). Screened positive SSD predicted low QOL in physical (B = −0.476, p < 0.001), social (B = −0.163, p < 0.001), emotional (B = −0.304, p < 0.001), and functional (B = −0.283, p < 0.001) well-being, as well as substantial concerns caused by breast cancer (B = −0.354, p < 0.001). Conclusion Screened positive SSD had strong mediating effects between psychological factors and quality of life among breast cancer patients. Additionally, screened positive SSD was a significant predictor of lower QOL among breast cancer patients. Effective psychosocial interventions for improving QOL should consider the prevention and treatment of SSD or integrated SSD caring dimensions for breast cancer patients.